Flight feather moult patterns and stable isotope analysis in the Woodland Kingfisher - Ramudzuli, Abigail (Department of Biological Sciences, 2025)
The Woodland Kingfisher Halcyon senegalensis is an intra-African migrant that is widely distributed south of the Sahara. Migrating populations have to undergo an annual cycle that includes two migrations between the breeding and non-breeding grounds, the renewal of feathers and reproduction. All the mentioned processes are energetically expensive and they need special physiological adaptations. I investigated the timing of moult by actively catching Woodland Kingfishers in the field and scoring them for moult. This showed that migrating Woodland Kingfishers that breed in South Africa do not moult their flight feathers while they are on their breeding grounds. Resident populations in Ghana and Uganda sampled between June and August, during their breeding season, were also not in moult, but some individuals were growing feathers that they had lost through mechanical damage. Moult data from the SAFRING database also showed no evidence of active moult for all adult birds in the southern Africa region, suggesting that they moult on the non-breeding grounds. This knowledge of moult allows us to use natural markers that are fixed in feathers to potentially infer where migrant birds spend their non-breeding period. To infer non-breeding grounds of the Woodland Kingfisher, I measured stable isotope ratios of carbon (δ 13C), nitrogen (δ 15N) and hydrogen (δ 2H) in primary (P1), secondary (S1) and tail (R1) feathers from birds caught in Ghana, South Africa and Uganda between 2015 and 2018 during the respective breeding seasons. Feather δ 13C of Woodland Kingfishers caught in Ghana suggest that these birds grow their feathers in areas dominated by C3 plants, whereas feathers from Woodland Kingfishers caught in Uganda and South Africa indicated that they moulted in areas dominated by C4 plants. This enables us to assign birds to different feeding areas. The δ 2H values were highest in South African feathers but not significantly different from the Ghanaian feathers, while the Ugandan δ 2H feather values were the lowest. The similar δ 13C and δ 2H values of feathers of birds from Uganda and South Africa suggests that the non-breeding grounds of the migrant South African population lies within the same isoscape band as that of Ugandan birds. δ 15N values, which indicate trophic levels, were similar for all the birds, suggesting that Woodland Kingfishers in Ghana, South Africa and Uganda forage on similar prey. The observations of colourringed Woodland Kingfishers in Uganda outside the breeding seasons confirm the Ugandan population to be sedentary and this enabled us to infer that the birds that were caught in this area were sedentary. While yet-unpublished telemetry data indicates Woodland Kingfishers that breed in South African spend their non-breeding period in areas around Chad, Sudan and Central African Republic. This region is within the same δ 13C isoscape as Uganda. The use of stable isotopes, especially when combined with other techniques, shows a lot potential as means of inferring the nonbreeding grounds of migrating Woodland Kingfishers. The approach of exploring moult patterns and analysing SI signals should be expanded for use on other intra-African migratory bird species because the migratory behaviour of most intra-African migrants still remains unknown.